2008
DOI: 10.1111/j.1469-8749.2008.03018.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of treatment when orthopaedic surgeons follow gait‐analysis recommendations in children with CP

Abstract: The aim of the present study was to assess the outcome of orthopaedic surgery in ambulant children with cerebral palsy, when the orthopaedic surgeons followed the recommendations from preoperative three-dimensional gait analysis. 55 children, mean age 10y 11mo, were clinically evaluated by orthopaedic surgeons who proposed a surgical treatment plan. After gait analysis and subsequent surgery, three groups were defined. In group A, there was agreement between clinical proposals, gait-analysis recommendations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 31 publications
1
52
1
1
Order By: Relevance
“…Filho et al observed a relationship between the degree to which gait analysis recommendations were followed and improvements in gait [17]. Lofterod and Terjesen reported positive kinematic outcomes in children who received surgical or non-surgical treatment consistent with gait analysis recommendations [18]. Molenaers et al found that patients managed with gait analysis had a lower prevalence of surgery at all ages and a lower rate of multiple surgeries than historical controls managed without gait analysis [19].…”
Section: Scorementioning
confidence: 99%
“…Filho et al observed a relationship between the degree to which gait analysis recommendations were followed and improvements in gait [17]. Lofterod and Terjesen reported positive kinematic outcomes in children who received surgical or non-surgical treatment consistent with gait analysis recommendations [18]. Molenaers et al found that patients managed with gait analysis had a lower prevalence of surgery at all ages and a lower rate of multiple surgeries than historical controls managed without gait analysis [19].…”
Section: Scorementioning
confidence: 99%
“…Gait analysis can be used to gain a better understanding of the causes and consequences of certain movement disorders. It also provides clinicians an opportunity to measure the effect of interventions aimed at restoring joint function and improving the performance of walking such as surgery [1], physical therapy [2] or pharmacological treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although Wren et al [8] admit that further high-quality studies, such as randomized controlled trials, are needed to ascertain the efficacy of gait analysis in improving a patient's condition, there are a few studies of interest. One such example is the study conducted by Lofterod et al [1]. This study demonstrated that an orthopedic surgical approach selected as a result of pre-operative gait analysis findings lead to better functional recovery compared to an approach chosen solely based on clinical assessment data.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of not undergoing GA, many patients may receive sub-optimal treatment, e.g. (Kay et al, 2000), (Lofterød and Terjesen, 2008).…”
Section: Introductionmentioning
confidence: 99%